Abusive Supervision and Links to Nurse Intentions to Quit. Issue 5 (15th August 2014) - Rodwell, John; Brunetto, Yvonne; Demir, Defne; Shacklock, Kate; Farr‐Wharton, Rod
Abstract Purpose To investigate forms of abusive supervision, namely personal attacks, task attacks, and isolation, and their links to outcomes for nurses, including job satisfaction, psychological strain, and intentions to quit. Design Cross‐sectional survey design. Data collected from July to November 2012. Methods Two hundred and fifty public sector nurses employed at five general acute Australian hospitals completed the survey (response rate of 33%). Findings Structural equation modeling on the forms of abusive supervision (personal, task, isolation) and nurse outcomes indicated goodness of fit statistics that confirmed a well‐fitting model, explaining 40% of the variance in intent to quit, 30% in job satisfaction, and 33% in strain. An indirect relationship from personal attacks to intentions to quit, via strain, was observed. Task attacks were related directly, and indirectly via job satisfaction, to increased intentions to quit. Surprisingly, isolation was positively related to job satisfaction. Conclusions Abusive supervision impacted nurse outcomes. Specifically, personal abuse had personal and health impacts; work‐focused abuse had work‐oriented effects. Applying appraisal theory suggests that personal attacks are primarily assessed as stressful and unchangeable; task‐oriented attacks are assessed as stressful, but changeable; and isolation is assessed as benign. The findings highlight the impact of abusive supervision, especially task attacks, on outcomes important to nurse retention. Clinical Relevance The findings can be used to devise programs to educate, train, and support supervisors and their subordinates to adhere to zero tolerance policies toward antisocial workplace behaviors and encourage reporting incidents.